2017
DOI: 10.1021/acsnano.6b08435
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrary-Shaped Graphene-Based Planar Sandwich Supercapacitors on One Substrate with Enhanced Flexibility and Integration

Abstract: The emerging smart power source-unitized electronics represent an utmost innovative paradigm requiring dramatic alteration from materials to device assembly and integration. However, traditional power sources with huge bottlenecks on the design and performance cannot keep pace with the revolutionized progress of shape-confirmable integrated circuits. Here, we demonstrate a versatile printable technology to fabricate arbitrary-shaped, printable graphene-based planar sandwich supercapacitors based on the layer-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 65 publications
0
65
0
Order By: Relevance
“…In addition, studies of electrochemical impedance spectroscopy (EIS) indicated PANI led to small changes in equivalent series resistances (ESR) and negligible changes in charge transfer resistance as shown in Figure S8 in the Supporting Information. [49][50][51] Although the thicker PANI coating could deliver higher capacitance, it is in sacrifice of fast charge/discharge rates, due to slower diffusion of ions and charges in the thicker PANI-based electrodes. The areal specific capacitance could achieve 11.76 mF cm −2 at scan rate of 10 mV s −1 while the areal energy density could reach 0.71 µWh cm −2 at power density of 40 µW cm −2 and remain at 0.58 µWh cm −2 at power density of 400 µW cm −2 .…”
Section: Wwwadvmattechnoldementioning
confidence: 99%
“…In addition, studies of electrochemical impedance spectroscopy (EIS) indicated PANI led to small changes in equivalent series resistances (ESR) and negligible changes in charge transfer resistance as shown in Figure S8 in the Supporting Information. [49][50][51] Although the thicker PANI coating could deliver higher capacitance, it is in sacrifice of fast charge/discharge rates, due to slower diffusion of ions and charges in the thicker PANI-based electrodes. The areal specific capacitance could achieve 11.76 mF cm −2 at scan rate of 10 mV s −1 while the areal energy density could reach 0.71 µWh cm −2 at power density of 40 µW cm −2 and remain at 0.58 µWh cm −2 at power density of 400 µW cm −2 .…”
Section: Wwwadvmattechnoldementioning
confidence: 99%
“…Indeed, there are many papers reporting deposition of active materials on flexible substrates for supercapacitor [30,31]. Specifically, Gao et al developed a cotton-textile-enabled asymmetric supercapacitor in which flower-like CoAl-LDH nanoarrays were grown on activated cotton textiles using a conventional hydrothermal method [32].…”
Section: Introductionmentioning
confidence: 99%
“…Equivalent series resistance (ESR), including electrolyte and electronic resistances,can be derived from high frequency region on the real axis. [57,58] Also,t his value (2.3 mWh cm À3 ) surpasses those of many recently reported planar MSCs, including onion-like carbon (1.1 mWhcm À3 ), [38] Ni@r-GO@MnO 2 (0.6 mWhcm À3 ), [39] PA NI nanowires (0.78 mWh cm À3 ), [40] and PA Ni/rGO (1.51 mWhcm À3 ), [41] and so on. [54] TheR agone plot in relation to the volumetric energy density and power density of mPPy/rGO-MSCs is shown in Figure 3f.R emarkably,m PPy/rGO-MSCs exhibit high volumetric energy density of 2.3 mWhcm À3 ,which compares well to that of lithium thin film battery (10 mWhcm À3 ), [55,56] and much higher than those of some commercial energy storage devices (Figure 3f).…”
mentioning
confidence: 59%